Managing health care costs : private sector innovations - Sullivan, Sean.; Ehrenhaft, Polly M. (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1984)
The present volume offers case studies in greater depth, focusing on two companies and two coalitions that have been pacesetters in the cost containment effort. The case studies exhibit a wide range of responses to rising costs by private payers. The second part of the book is an edited transcript of an AEI (American Enterprise Institute) seminar on private sector initiatives in health care, held in July 1983.
ne 05/06/2018
Loans
Keywords: Health insurance; Medical care